METAL COMPLEXES OF 3-CHLORO-4-HYDRAZINO-CARBONYL-METHOXY-BENZENESULFONDIBUTHYLAMIDE - ANCA MOCANU; CORINA CERNATESCU (Chemical Industry and Chemical Engineering Quarterly, 2008)
By taking the biological activity of 3-chloro-4-hydrazinocarbonyl-methoxy-benzenesulphondibuthylamide and of some transitional metals (Cu, Co, Cr, Fe, Mn, Ni, Sn) into account we considered it useful to capitalize the already obtained hydrazide by complexion reactions with various metallic salts. The reaction was carried out in the organic solvent medium, by heating under stirring. The obtained products were purified by recrystallization from organic solvents (especially ethanol) and characterized by means of melting points, elemental analysis and spectral measurements.